Princípio federativo e o disciplinamento constitucional dos recursos hídricos - Souza Filho, Marcos José Nogueira de (2008)
Legislative abilities in substance of water resources of ambiguous form, attempt to be transparent, from the privative capacity of the Union to legislate about the waters (art. 22, IV), the legal impossibility of the State to legislate on the subject. The proper Constitutional Text occurs that such conjuncture if does not justify, mainly because conferred to the State the property of the water resources (art. 26, I), the example of what it also made in face of the Union (art. 20, II). However, the water resources had started to exhibit the condition of public easement of the people, that consists of that can indistinctly be usufructed by any person, fitting to the Public Power - in case to the agencies and component entities of the water Resources Management National System – the management, the control and the attention of the private activities that involve the water use. Such use is, in rule, conditional the previous grant for the Public Power, of onerous character in function of the quality of waters as endowed well with economic value, in observance the beginning of the polluter-payer agent. Everything this indicates more that the water resources constitute public goods, if not admitting the legally hypothesis of municipal water e, much less, particular. Doctrinal, the legislative ability and the dominical question do not count on unanimity enter the authors of the Constitutional law, Administrative law, Civil law e, mainly, Environment law. The present academic work, in these terms, considers to unmask it the respective indicated solutions of the problematic ones, from a taking of critical positioning, exhausting and based, rejecting fixedly the points of view favorable (a) to the privative ability of the Union to legislate on water resources and (b) to the constitutional possibility citizens the particular property on the water.